La observación: un medio para mejorar la práctica docente - Gonzaga Martínez, Wilfredo (2002)
In the field of education, particularly in educational evaluation, educators resort to tests and other instruments that are very valuable, but do not accomplish the objective of capturing a series of aspects of the individual at a specific moment and the educational process in the classroom. Among these aspects one may mention attitudes, behavoir and development which are important elements to be considered when expressing a value judgement in relation to the student's learning and teacher's performance. To contribute to a better valuing, observation fulfills a major important role. It allows to complement the information gathered by measuring instruments such as written tests, grading scales, matching lists, and anecdotal records, among others. However, this kind of observation requires systematization because it does not refer to a contemplative attitude; on the contrary, it needs the acting of the individuals upon their environment, a planning and a corroboration of the impact of their actions.